ANALISIS PENGAKUAN PENDAPATAN ATAS KONTRAK INDIBIZ PADA PT TELEKOMUNIKASI INDONESIA AREA MAGELANG - Ahmad Sirojuddin Al Rosyid; Agustina Prativi Nugraheni (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
PT Telkom Indonesia Witel Yogya Jateng Selatan Area Magelang is an information and communication technology institution that is ready to serve the needs of the community for connectivity and digitalization. This study aims to analyze the conformity of revenue recognition on Indibiz service contracts with the provisions stipulated in PSAK 115 concerning revenue from contracts with customers at PT Telkom Indonesia Witel Yogya Jateng Selatan Area Magelang. Compliance with revenue recognition on service contracts with the provisions of PSAK 115 is very important to ensure the security of customers and service providers. The research used a qualitative method with a case study approach, which includes in-depth interviews with related parties, direct observation, and document analysis. The results of this study indicate that revenue recognition on Indibiz service contracts is carried out monthly in accordance with the method of providing continuous services over time, so that the practice is in accordance with the provisions of PSAK 115.